Analisis Halal Supply Chain Terhadap Kinerja Manajerial pada Produsen Makanan di Kota Surakarta - Dewi, Sholikhah Ratna (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
The supply chain is an important thing for businesses to pay attention to because it will affect their performance. Halal products must pay attention to the supply chain in accordance with halal criteria. For this reason, this study has the aim of analyzing the effect of halal supply chain management on the managerial performance of food product business actors in the city of Surakarta. This research is included in quantitative research by utilizing a questionnaire method which will be used to obtain information and research data. The population of this study consisted of business actors who already had halal certification with a total of 297 business actors. Determination of the sample utilizes the slovin formula so that the results of the calculation are 170 business actors used as research samples. The data source is obtained from documentation and questionnaire data. To conduct further analysis, this study utilizes linear regression analysis to obtain hypothesis results. The results of this study indicate that the halal supply chain regression value has a positive and significant effect partially or simultaneously on the managerial performance of food product MSME players in Surakarta city. As much as 77% is directly influenced by the supply chain of these things and the correlation it causes is 0.877.